Bottom gate ZnO-TiO2 thin film transistor fabrication using a Rf-sputtering technique on Si and glass substrates. (2021) - Surve, Sachin; Banerjee, M.K.; Sachdev, Kanupriya
Abstract: ZnO thin films were fabricated by an RF-sputtering deposition technique on Si and Glass substrate and then was used as the active semiconductor material in thin-film transistors (TFTs). The TFTs were fabricated in a bottom gate with top contact electrode structure with high-k TiO2 as the gate insulator and Au used for the source and drain electrodes but Al for the gate electrode. TFTs were annealed at 500 °C for 1 h using sputtering inside the substrate heating facility. The TFT with a W/L (4/1) channel ratio found high field-effect mobility of is 5.19 cm 2 /Vs and drain current on–off ratio at 10 7 with a low threshold voltage.